Socio-Economic Attributes of Residents as Drivers of Adaptation to Climate Change Effects in a Nigerian Traditional Urban Center - , Abel Omoniyi Afon, Olanrewaju Timothy Dada, Gbemiga Bolade Faniran (Archives of Current Research International, 2016)
This paper examined residents’ socio-economic attributes as drivers of adaptation to climate change effects in Ibadan metropolis, Nigeria. Through systematic random sampling, primary data were obtained from 442 household heads in the core, transition and sub-urban residential areas. The study established that residents' socio-economic characteristics varied along the line of the identified residential areas. The major adaptive strategies adopted were reactive rather than anticipatory. The three most important adaptive strategies measured on a 5-point likert scale were ‘repair/replace damaged properties’ (3.76), ‘eliminate deliberate dumping of waste in drain’ (3.72) and 'listening to information about climate change’ (3.70). Adaptive strategies in the different residential areas were similar, but different in magnitude as denoted by the resident response index Residents in different socio-economic groups, especially in the education status and income groups exhibited different levels of mean score, but showed that same responses were given to the same climate change effects. The study concluded that residents were susceptible to similar adverse effects of climate change and that the contents of environmental education to all residents may have to be the same, though, with varied methodology due to the significant difference in socio-economic attributes.